The technician's EMI handbook : clues and solutions - Carr, Joseph J. (Newnes, 2000)
A hands-on guide to finding the sources of electromagnetic interference and then fixing the problems. Includes basic theory of EMI as well as detailed explanations of why this problem is becoming more serious as the international scope of the communications and electronics industries grow. This book is not a textbook, but rather a handbook that will become a constant source of reference for anyone who runs into trouble with EMI. Includes chapters on grounding, circuit shielding and filtering, preventing EMI in circuit design, as well as EMI sources such as power lines, transmitters, televisio.